"Viewed with suspicion, considered idle and mocked‐working caregiving fathers and fatherhood forfeits". Issue 5 (27th April 2022) - Kelland, Jasmine; Lewis, Duncan; Fisher, Virginia
Abstract: Existing academic literature consistently points to a changing role for modern fathers in which they take an egalitarian role in the caregiving responsibilities for their children. Despite this, fathers are observed to continue to dominate the realms of full‐time working, aligning to more traditional breadwinning mentalities than such trends might suggest, raising questions around inequality. Fathers at work have previously been found to encounter challenges within the workplace when they alter, or consider altering their work patterns due to caregiving responsibilities. Employing a sample of working parents and managers, this paper explores how caregiving fathers are perceived within organizations and in considering their experiences, provides a nuanced and detailed understanding of the ways in which mistreatment for caregiving fathers manifests within contemporary UK workplaces. Caregiving fathers are found to face specific challenges termed "fatherhood forfeits" such as perceived idleness, suffering mockery, and being viewed with suspicion by male and female co‐workers. Actions are proposed to address "fatherhood forfeits" that include specific organizational training interventions and the importance of workplace role modeling.